Introductory Statistics - Ross, Sheldon M (India Elsevier, 2009)
This second edition has many new and updated examples and exercises, new sections cover the linear regression model, quality control, and more, clear writing and illustrations help students understand statistical methods and reasoning, learning aids include chapter introductions, summaries, and key terms, along with sections on historical information and current applications
This is the second Edition
11
Keywords: Estimation -- Statistics; Introductory Statistics; Probability -- Statistics